More is more: Livelihood interventions and child labor in the agricultural sector - Vera Chiodi; Verónica Escudero (International Labour Organization (ILO), 2020)
What works to reduce child labor in agriculture? In this paper, we evaluate two randomized livelihood intervention programs, aimed to reduce child labor, particularly in its most exploitative forms, in rural areas of Peru and the Philippines. In the first randomized experiment, we evaluate a livelihood intervention provided to farmers in Peru that use the labor of their children on their family farms, accompanied by an education intervention aimed to improve the quality of schools and an awareness-raising intervention. In the second randomized experiment, we evaluate the incremental effect of the livelihood intervention implemented within a similar program in the Philippines, focused on the sugarcane agricultural sector. We find that when livelihood interventions were provided alone, they did not manage to improve economic conditions, and hence generally failed to reduce child labor rates in rural areas. However, when the livelihood intervention was combined with measures to improve the quality of education in Peru, we see a reduction in hazardous child labor and child labor overall. Awareness-raising interventions, aimed at changing the perceptions of parents through community interaction, appear to have also had an effect in the reduction of child labor, and these effects were reinforced by education interventions. Results indicate that a comprehensive approach including livelihood support with education and awareness-raising components is a more effective way to reduce child labor and hazardous labor for children in the agricultural sector.
Keywords: 330; child labour; rural employment; livelihoods; child workers; hazardous work; education; agriculture; rights of the child; social policy